Development and validation of an LC‐MS/MS method for simultaneous determination of piperaquine and 97‐63, the active metabolite of CDRI 97‐78, in rat plasma and its application in interaction study. Issue 2 (14th May 2015) - Wahajuddin, Muhammad; Singh, Sheelendra Pratap; Taneja, Isha; Raju, Kanumuri Siva Rama; Gayen, Jiaur Rahman; Siddiqui, Hefazat Hussain; Singh, Shio Kumar
Abstract : Piperaquine‐dihydroartemisinin combination is the latest addition to the repertoire of ACTs recommended by the World Health Organization (WHO) for treatment of falciparum malaria. Due to the increasing resistance to artemisinin derivatives, CSIR‐CDRI has developed a prospective short acting, trioxane antimalarial derivative, CDRI 97‐78. In the present study, a liquid chromatography‐electrospray ionization‐tandem mass spectrometry (LC–ESI‐MS/MS) method for the simultaneous quantification of piperaquine (PPQ) and 97‐63, the active metabolite of CDRI 97‐78 found in vivo, was developed and validated in 100 μL rat plasma using halofantrine as internal standard. PPQ and 97‐63 were separated using acetonitrile:methanol (50:50, v / v ) and ammonium formate buffer (10 mM, pH 4.5) in the ratio of 95:5( v / v ) as mobile phase under isocratic conditions at a flow rate of 0.65 mL/min on Waters Atlantis C18 (4.6 × 50 mm, 5.0 µm) column. The extraction recoveries of PPQ and 97‐63 ranged from 90.58 to 105.48%, while for the internal standard, it was 94.27%. The method was accurate and precise in the linearity range 3.9–250 ng/mL for both the analytes, with a correlation coefficient (r) of ≥ 0.998. The intra‐ and inter‐day assay precision ranged from 2.91 to 8.45% and; intra‐ and inter‐day assay accuracy was between 92.50 and 110.20% for both the analytes. The method was successfully applied to study the effect of oral co‐administration of PPQ on the pharmacokinetics of CDRI 97‐78 in Sprague‐dawley rats and vice versa. The co‐administration of CDRI 97‐78 caused significant decrease in AUC0–∞ of PPQ from 31.52 ± 2.68 to 14.84 ± 4.33 h*µg/mL. However, co‐administration of PPQ did not have any significant effect on the pharmacokinetics of CDRI 97‐78. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The validated LC‐ESI‐MS/MS method has a short run time of 5 minutes and sesitivity of 3.9 ng/mL for piperaquine as well as CDRI 97‐78. Pharmacokinetic study results show that piperaquine systemic exposure was reduced significantly when co‐administered with 97‐78, which was not significantly affected.